Pengaruh pemupukan NPK terhadap pertumbuhan bibit jabon putih Anthocephalus cadamba (Roxb.) Miq. - Ramli Sapsuha; Alfonsius Thomas; Marthen T. Lasut; Johanes A. Rombang (COCOS, 2015)
ABSTRACTInfluence fertilization of NPK to growth of Jabon Putih seeds Anthocephalus cadamba (Roxb.) Miq.This research studied the effect of NPK (15 : 15 : 15) on seedlings growth of Anthocephalus cadamba. The research used Randomized Block Design (RBD) with five treatments and five replications. Treatment A as a control, treatment B 0,25 g NPK/plan, treatment C 0,50 g NPK/plant, treatment D 0,75 g NPK/plant and treatmen E 1 g NPK/plant, given every two weeks for two months. Plant media of this research was soil, sand and chicken manure with ratio7 : 2 : 1 based on volume. The measured variables were crop height, crop bar diameter and the number of leaf. The results showed that the applications of NPK fertilizer on Jabon putih seedling gave significantly different result to the crop height accretion at firstand second weeks and for the crop bar diameter at seventh week and eighth week, while the number of seedling leaf of Jabon Putih was not significantly different. The growth of crop was better in treatment C comparing to the other treatments.Keyword : Jabon Putih, NPK 15 : 15 : 15